MicroRNAs in Head and Neck Cancer - Keziah John; Jennifer Wu; Bing-Wei Lee; Camile S. Farah (Hindawi Limited, 2013)
microRNAs (miRs) are small noncoding single-stranded RNAs, about 19-25 nucleotides long. They have been shown to be capable of altering mRNA expression; thus some are oncogenic or tumour suppressive in nature and are regulated by cellular and epigenetic factors. The molecular pathogenic pathway of many cancers has been modified since the discovery of miRs. Head and neck squamous cell carcinoma (HNSCC), the sixth most common cancer in the world, has recently been associated with infection by the human papillomavirus (HPV). miR expression profiles are altered in the transition from dysplasia to carcinoma, with some changes being specific to the underlying risk factor. This difference is particularly significant in HPV-positive HNSCC where host miRs are modulated by the virus, creating a different profile to HPV-negative HNSCC. Saliva, as an easily collected proximal biofluid containing numerous miRs, presents an attractive noninvasive diagnostic tool in detecting HNSCC and determining prognosis. Furthermore, miRs may play a role in the analysis of surgical margins for residual tumour extension and in the development of novel miR-based therapeutic targets and agents.